Alpha-1-antitrypsin (SERPINA1) mutation spectrum: Three novel variants and haplotype characterization of rare deficiency alleles identified in Portugal. (July 2016) - Silva, Deolinda; Oliveira, Maria João; Guimarães, Miguel; Lima, Ricardo; Gomes, Sílvia; Seixas, Susana
Abstract: Background: Alpha-1-antitrypsin deficiency (AATD) is a genetic condition caused by SERPINA1 mutations, which culminates into lower protease inhibitor activity in the serum and predisposes affected individuals to emphysema. Clinical manifestations of AATD are often associated to ZZ (p.Glu342Lys) and SZ (p.Glu264Val) genotypes and less frequently to rare deficiency or null alleles in heterozygous and homozygous states. Methods: We sequenced SERPINA1 (approximately 8 kb) and genotyped two microsatellites located upstream and downstream of the gene (195 and 5.6 kb, respectively) in a cohort of 51 AATD patients found to carry different rare alleles. A meta-analysis of SERPINA1 mutation spectrum was also performed. Results: We detected a total of 14 rare alleles including 3 defined by novel mutations (p.Glu162Gly, p.Arg281Lysfs*17 and p.Met374Leufs*19) and 11 characterized by previously described variants (c.-5+2dupT, p.Arg39Cys, p.Phe52del, p.Thr68Ile, p.Asp256Val, p.Leu263Pro, p.Glu264Val, p.Leu353Phefs*24, p.Pro369Ser and p.Pro369Leu) but in several instances differing in their molecular backgrounds. So far, SERPINA1 has 132 low-frequency variants (<1%), where AATD mutations are not evenly distributed across the three-dimensional structure and tend to cluster in functional domains like the gate or the shutter. Conclusion: The contribution of rare SERPINA1 alleles into AATD should not be neglected in the diagnosis practice given there is a wide spectrum of variants originated by mutation and sometimes shuffled between chromosomes by recombination. Even though many of the rare variants are likely to be recent and population specific others seems to be as old as the Z allele and dispersed across European populations. Highlights: Fourteen rare alleles associated to AATD were found in the Portuguese population. MMalton and MPalermo alleles have arisen by the recurrence of p.Phe52del mutation. Five pathogenic mutations segregate at low-frequencies among Europeans. AATD causing mutations tend to cluster in SERPINA1 shutter and gate domains.